Pemanfaatan Media puzzle untuk meningkatkan kemampuan peserta didik pada materi teks deskripsi melalui pendekatan Culturally Responsive Teaching (CRT) - Keni Apriliano; Juaidah Agustina (JURNAL ILMIAH NUSANTARA, 2024)
The study was designed to determine the benefits of puzzle learning media on descriptive text material through a connecting Culturally Responsive Teaching (CRT) approach. Puzzle learning media is learning media in the form of pieces of paper that are separated and returned to their integrity, this learning media is very useful for students, integrated into the Culturally Responsive Teaching (CRT) learning approach with pictures about culture, this can strengthen cultural identity with descriptive text material to described by students.